Integrasi Strategis untuk Keunggulan Akademik: Memanfaatkan COBIT dan PMBOK dalam Praktik Audit dan Manajemen Proyek - Moch Yasin; Prasasti Karunia Farista Ananto; Bramasta Kurnia Aji; Ilham; Mohammad Khusnu Milad; Suryani DA (Postgraduate, University of Mataram, 2024)
This research aims to explore the strategic integration of the COBIT (Control Objectives for Information and Associated Technologies) and PMBOK (Project Management Body of Knowledge) frameworks in optimizing audit and project management practices in the academic world. This research draws on practice-based case studies as well as existing literature to highlight the benefits and strategies for implementing the strategic integration of COBIT and PMBOK in the academic world. Aligning governance with project management principles, an institution such as higher education can enhance their efforts to achieve academic excellence. COBIT and PMBOK integration strengthens audit practices by ensuring regulatory compliance, practical risk assessment, and robust controls. It also promotes a structured approach to project management, improved planning, resource allocation, risk mitigation, and communication. Collaboration between the audit and project management teams is facilitated through this integration, enabling effective communication, coordination and knowledge sharing. Colleges can then position themselves strategically to achieve academic excellence, aligning their operations with strategic goals and driving efficiency, transparency and accountability. Based on this discussion, it can be concluded that integrating the COBIT and PMBOK frameworks can advance the efforts of an institution, namely higher education, to achieve academic excellence and strengthen leadership in the field of education.